The formin FMNL2 plays a role in the response of melanoma cells to substrate stiffness - Joshua D. Clugston; Sarah Fox; James L. Harden; John W. Copeland (BMC Molecular and Cell Biology)
Abstract Background Cells constantly sense and respond to changes in their local environment to adapt their behaviour and morphology. These external stimuli include chemical and mechanical signals, and much recent work has revealed the complexity of the cellular response to changes in substrate stiffness. We investigated the effects of substrate stiffness on the morphology and motility of A2058 human melanoma cells. FMNL2, a formin protein associated with actin cytoskeleton dynamics, regulates melanoma cell morphology and motility, but its role in stiffness sensing remains unclear. This study examines how A2058 cells respond to substrates of varying stiffness and evaluates the impact of FMNL2 depletion on these responses. Results We found that with increasing substrate stiffness the cells transitioned from a rounded cell morphology to progressively more elongated morphologies with a concomitant increase in actin stress fiber alignment. Depletion of FMNL2 expression amplified these morphological changes, with knockdown cells showing consistently greater elongation and more pronounced stress fiber alignment compared to controls. Notably, the orientational order parameter (S) revealed higher alignment of actin filaments along the cell’s long axis in knockdown cells. Substrate stiffness also affected cell motility, indicated by an apparent optimal stiffness that maximized motility followed by a notable decrease in distance travelled during migration on progressively stiffer substrates. This decrease was largely attributable to a decrease in the time the cells spent in motion as the substrate stiffness increased. FMNL2 depletion significantly exacerbated this effect, with knockdown cells traveling shorter net distances and spending less time moving across all substrates. Conclusions This study demonstrates that substrate stiffness profoundly influences A2058 melanoma cell morphology and motility, with FMNL2 playing a pivotal regulatory role. Our observations suggest that FMNL2 is critical for maintaining motility and morphological adaptability under increased stiffness. Loss of FMNL2 enhanced stress fiber alignment and cell elongation while impairing motility, particularly on stiff substrates, revealing FMNL2 as a mechanosensitive effector. This work highlights the need to study metastatic cell behaviour on substrates with biologically relevant properties and provides the foundation for future effort to determine the mechanism by which FMNL2 participates in the melanoma cell response to substrate stiffness.